Relationship of Depth of Invasion with Lymph Node Metastasis in Advanced Oral Cavity Squamous Cell Carcinoma (Bangladesh Journal of Otorhinolaryngology, 2026)
Background: Depth of invasion (DOI) is a key histopathological marker in oral cavity squamous cell carcinoma (OCSCC), indicating tumor aggressiveness and predicting cervical lymph node metastasis, particularly in advanced cases with higher occult spread risk. As early-stage (T1, T2) tumors have well-documented patterns and predictable outcomes, this study focuses on advanced-stage (T3, T4) OCSCC, where DOI shows greater variability and stronger influence on staging and treatment planning.Methods: This cross-sectional study was conducted in the Department of Otolaryngology-Head & Neck Surgery, Bangladesh Medical University, Dhaka and National Institute of Ear, Nose and Throat, Dhaka for 18 months. A total number of 30 cases of advanced oral cavity Squamous cell carcinoma were enrolled for the study on the basis of inclusion and exclusion criteria. Post operative histopathological Depth of invasion were analyzed to predict the cervical node metastasis. Results of the study were expressed as mean, standard deviation (± SD), frequency and percentages. Unpaired students t-test and chi-square test was performed as applicable. p-value 10 mm (p = 0.002). Mean DOI was significantly greater in LN-positive patients compared to LN-negative cases (p = 0.000).Conclusion: Depth of invasion is strongly related with cervical lymph node metastasis and serves as a reliable predictor for staging, surgical planning, and prognosis in OCSCC. Incorporating DOI into routine histopathology and imaging can improve treatment decisions and patient outcomes.Bangladesh J Otorhinolaryngol 2026; 32(1): 5-12